Education Of Social Workers In Poland And Slovakia - Beata Szluz (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The presented article aims at clarifying the situation in the field of social workers university education in Poland and Slovakia, taking into account social and political transformations in both countries. The first part of the article presents the origins of the beginning and development of social workers university education in Poland. The second part, based on an analysis of available governmental conceptual and strategic documents, clarifies the crucial influence of the state policy in the field of university education on the current state of social workers education in Slovakia. The third part, outlines a vision and the priorities as well as points to appropriate tools adopted on the level of national association of educators in the field of social work.